THE IMPLEMENTATION OF EDUPRENEURSHIP OF EFL STUDENTS IN THE INDONESIAN CONTEXT - Aswin Abbas; Muhammad Astrianto Setiadi; Marlia Marlia; Andi Adisaturrahimi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
The growing knowledge about edupreneurship in tertiary institutions, makes the goal not only to lead students to become entrepreneurs but more to form the character of edupreneurship, including EFL students. This study aims to elaborate on how to implement edupreneurship by EFL students in the Indonesian context. This descriptive research method uses a qualitative, semi-interviews with two focals participants, due to their experiences as business owners in the world of entrepreneurship education, also have received edupreneurship courses in college. The author wants to see how they implement their business and related to EFL. The findingsfrom interview sections showed that in implementig edupreneurship had varius aspects, the managerial and process, further other aspects appeared also, like environment, technology and of course an entrepreneurship course, took an important rules in running the bussiness. In terms of EFL, edupreneurship get involved in. By this finding, of course, the business they are currently running can be a trigger for other students who want to start passions in the world of edupreneurship. Keywords: Edupreneurship, EFL students, indonesian context